Design optimization of mesh antennas for on-orbit thermal effects. (1st June 2020) - Nie, Rui; He, Baiyan; Yan, Shaoze; Ma, Xiaofei
Highlights: An optimization design method for cable network antennas is proposed to reduce the on-orbit thermal errors and relieve the burden of shape pre-adjustment before launch. The thermal-structural model considering the thermal deformation and elastic deformation of the truss and cable network is established. The antenna's uneven temperature filed at typical orbital positions is calculated, and the influences of the on-orbit thermal effects on the antenna surface accuracy and tension distribution are discussed. Numerical examples are provided, and the results proved that the antenna's on-orbit surface accuracy and tension distributions were improved effectively by the optimization. Abstract: Cable network antennas are widely used in space missions, and high requirements on the reflector surface accuracy should be met to achieve reasonable electromagnetic performance. As the form of the cable network is dependent on forces and vice versa, the optimization design for the antenna's cable forces is extremely important. The current optimization methods are usually conducted under ambient temperature, ignoring the shape errors caused by the on-orbit thermal effects in space. Besides, the application of the active shape adjustment method is also limited by the on-orbit measurement and on-orbit control techniques at present. To reduce the on-orbit thermal disturbances and relieve the burden of shape pre-adjustment before launch, we proposed an optimization design method focusing on the on-orbit performances. The antenna's uneven temperature filed at typical orbital positions was calculated based on the heat radiation and conduction theories. The thermal-structural model considering the cable network's and the truss's thermal deformation and elastic deformation was established. For the optimization, the cable force densities were chosen to be the optimization variables, the antenna's shape errors at typical orbital positions were taken as the objectives, and the tension distributions at these orbital positions were considered as the constraint conditions. Numerical examples demonstrated that the proposed method improved the antenna's on-orbit surface accuracy effectively. This work provided ideas and solutions for the cable network's optimization design considering the on-orbit performances in the space environment. Garphical abstract: Image, graphical abstract